Impact of Financial Inclusion on Economic, Environmental, and Social Sustainability of Asian Emerging Markets - Hussain, Rida; Iqbal, Zafar; Nazir, Syeda Saba; Hussain, Munawar (NUML International Journal of Business & Management, 2025)
Promoting financial inclusion helps achieve sustainability, but the primary challenge is achieving this goal in emerging Asian markets. Therefore, this study investigates the relationship between financial inclusion and sustainability in developing Asian countries, an underexplored area in the existing literature. The study examines the impact of various financial transactions on sustainability using panel data from 1990 to 2023 sourced from the IMF Financial Inclusion Surveys, World Bank Indicators (WBI), and financial inclusion indicators. The study examines the impact of different financial transactions on sustainability. The study population comprises emerging markets in Asia. The sample size consists of ten Asian emerging markets. The study used a quantitative research design with secondary data. A deductive approach was employed, utilizing regression analysis techniques such as fixed effects models and the Generalized Method of Moments (GMM). The results indicate that money deposits have a positive influence on economic sustainability but have a detrimental effect on environmental and social sustainability. Money transfers exhibit no significant impact on sustainability, while money withdrawals are found to positively affect economic sustainability but negatively impact the environmental and social dimensions. This study offers a theoretical contribution by shedding light on the complex consequences of financial inclusion and contradicts the widely held belief that all financial activity results in positive sustainability results. To strengthen the role of financial inclusion in sustainable development, policymakers should adopt socially responsible financial policies and green banking initiatives to promote a balance between sustainability and financial development.